2021
DOI: 10.5125/jkaoms.2021.47.2.99
|View full text |Cite
|
Sign up to set email alerts
|

A critical assessment of the medication-related osteonecrosis of the jaw classification in stage I patients: a retrospective analysis

Abstract: Objectives It is unclear whether the extent of intraoral mucosa defects in patients with medication-related osteonecrosis of the jaw indicates disease severity. Therefore, this study investigated whether mucosal lesions correlate with the true extent of osseous defects in stage I patients. Materials and Methods Retrospectively, all patients with stage I medication-related osteonecrosis of the jaw who underwent surgical treatment between April 2018 and April 2019 were en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…40 However, 11 out of 20 patients (55.0%) were clinical stage I. According to AAOMS staging, stage I patients have only necrotic bone exposure without symptoms such as inflammation and infection before surgery, 41 and the symptoms of osteonecrosis in their study were mild, which was not sufficient to demonstrate the effectiveness of the mylohyoid muscle flap for wound closure in advanced MRONJ lesions. Furthermore, Ristow et al reported the results of applying the mylohyoid muscle flap double-layer closure technique to close wounds after resection of a total of 68 mandibular MRONJ lesions in 57 patients; mucosal healing was achieved in 6 out of 11 stage III lesions (54.5%) at 8 months postoperatively, which resulted in a higher rate of surgical success in early stage lesions compared to advanced stage III lesions.…”
Section: Discussionmentioning
confidence: 93%
“…40 However, 11 out of 20 patients (55.0%) were clinical stage I. According to AAOMS staging, stage I patients have only necrotic bone exposure without symptoms such as inflammation and infection before surgery, 41 and the symptoms of osteonecrosis in their study were mild, which was not sufficient to demonstrate the effectiveness of the mylohyoid muscle flap for wound closure in advanced MRONJ lesions. Furthermore, Ristow et al reported the results of applying the mylohyoid muscle flap double-layer closure technique to close wounds after resection of a total of 68 mandibular MRONJ lesions in 57 patients; mucosal healing was achieved in 6 out of 11 stage III lesions (54.5%) at 8 months postoperatively, which resulted in a higher rate of surgical success in early stage lesions compared to advanced stage III lesions.…”
Section: Discussionmentioning
confidence: 93%
“…It is certainly debatable whether the current AAOMS staging [ 12 ] correctly reflects the defect size. Recent work has shown that this is not the case [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the research, individuals with MRONJ have significant rates of recurrence/dehiscence following surgical resection, which results in more hospital stays and subsequent operations [48]. As a result, numerous methods for improving the existing therapy have been tried, but they have not yet been used in clinics [49]. Examples include altering the flap design or using intraoperative imaging to guide bone surgery.…”
Section: Discussionmentioning
confidence: 99%